Working in partnership: making it happen for high risk personality disordered offenders. Issue 3 (10th August 2015) - Logan, Caroline; Ramsden, Jo
Abstract : Purpose: – The implementation of the Offender Personality Disorder (OPD) strategy requires partnership between NHS providers and custodial and community-based practitioners in the National Offender Management Service (NOMS). What this partnership looks like is dependent on the nature and resources of involved services. However, what it is meant to achieve – reduced reoffending, a more knowledgeable workforce, and a more engaged client group – is clearer. It is fundamental to the OPD strategy that these outcomes are delivered through partnership so as to minimise harmful transitions between services, and to effectively share the expertise required for the holistic case management of personality disordered (PD) offenders. The paper aims to discuss these issues. Design/methodology/approach: – The implementation of the OPD strategy is ongoing, and data will be forthcoming in due course that will allow for the empirical test of the hypothesis that working together is better than working separately. However, with the emphasis on public protection and workforce development, some of the crucial partnership issues may remain less well understood or explored. This paper overviews the services in which the authors are involved, describing their initiation and operation. Findings: – The paper articulates how NHS/NOMS partnerships have been developed and experienced. Practical implications: – The paper concludes with a discussion of a number of principles for partnership work in relation to the OPD strategy. Originality/value: – This paper is intended to assist developing services to make the most of collaborative working across the PD pathway in England and Wales.